The “Implementation of Multicultural Pancasila-Based Arabic Language Learning to Enhance Religious Moderation among Students in the Arabic Language Education Department.” - Ahyal khairi; Muh. Wasit Achadi; Adhi Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the implementation of a Pancasila-based multicultural Arabic language learning model and its contribution to strengthening religious moderation among students in the Arabic Language Education Department at UIN Sunan Kalijaga Yogyakarta. Responding to increasing social diversity and digitalization in higher education, this research highlights the need for integrating linguistic competence with multicultural and national values. Using a qualitative field research design, data were collected through semi-structured interviews with lecturers and students, classroom observations, and documentation of instructional materials and lesson plans. The findings show that Pancasila values particularly tolerance, cooperation, unity, and social justice are systematically integrated during the planning, instructional processes, and assessment phases. Students perceive the model as relevant and effective for enhancing intercultural understanding, although challenges remain in harmonizing diverse backgrounds, digital readiness, and group dynamics. The study also reveals that this learning model significantly contributes to strengthening students’ religious moderation, reflected in increased tolerance, openness to diversity, and inclusive religious attitudes. Arabic, as the language of Islamic sources, becomes a medium for developing moderate interpretations and preventing textual extremism. However, the study suggests the need for more standardized evaluation tools for measuring religious moderation outcomes. This research provides theoretical contributions by integrating multicultural pedagogy with Pancasila-based values in Arabic education and offers practical implications for curriculum development, lecturer training, and national policies related to religious moderation.